Detection of the single nucleotide polymorphism (rs2227307) in the human interleukin 8 gene using a pcr-rflp assay - Kim, Yeon Jung [UNESP]; Viana, Aline Cavalcanti; Tfaile Corbi, Samia Cruz; de Carvalho Curtis, Karen Maria [UNESP]; Renzi, Rivelto; Orrico, Silvana Regina Perez [UNESP]; Cirelli, Joni Augusto [UNESP]; Scarel-Caminaga, Raquel Mantuaneli [UNESP] (Universidade Federal de Uberlândia (UFU), 2009)
Interleukin 8 (IL-8) is a chemokine that acts as a potent chemoattractant for neutrophils. Single nucleotide polymorphisms ( SNPs) in the human IL8 gene have been investigated in many disease association studies. We have developed a different PCR-RFLP (Polymerase Chain Reaction - Restriction Fragment of Length Polymorphism) assay for genotyping the SNP (rs2227307) in the IL8 gene. This method was used for typing 147 white healthy Brazilian individuals, whose DNA was obtained from buccal epithelial cells and extracted with phenol: chloroform: isoamyl alcohol. Genomic DNA was amplified by PCR using a conventional thermal cycler. The PCR products ( 573 bp) were submitted to RFLP reactions. The RFLP fragments were analyzed in a 4% agarose gel stained with ethidium bromide. The genotype distribution observed in this study was consistent with the assumption of Hardy-Weinberg equilibrium and was similar (p=0.30) to those reported for other white populations in the SNP Database of the National Center for Biotechnology Information (NCBI). Because the PCR-RFLP method presented here was efficient, low cost, reproducible and convenient for laboratories with a limited level of technology worldwide, it should be useful for genotyping in case-control association or population genetic studies.
Keywords: Single Nucleotide Polymorphism; Interleukin 8; PCR-RFLP assay